2019
DOI: 10.1111/mam.12171
|View full text |Cite
|
Sign up to set email alerts
|

A mixed model of the evolution of polygyny and sexual size dimorphism in mammals

Abstract: The theory of sexual selection is the most widely accepted theory explaining the evolution of mating systems and secondary sexual characters. Polygyny is the most common mating system in mammals, and there is a strong correlation between the degree of polygyny and the degree of sexual size dimorphism skewed towards males. Sexual selection theory posits that polygyny in mammals has evolved through direct, precopulatory, intrasexual selection in males, and that sexual size dimorphism is a result of male competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 83 publications
(71 reference statements)
3
33
1
Order By: Relevance
“…Male adulticide was significantly and positively associated with male-biased size dimorphism in all analyses (table 1), being more prevalent in dimorphic species than in monomorphic ones (61% versus 44%, respectively, using 10% size difference between sexes as a cut-off point to consider a given species as dimorphic) [24]. Sexual size dimorphism is considered a direct consequence of sexual selection in mammals [24,25], and it is widely used as a surrogate of the intensity of the sexual selection operating on each species [25]. Mammals for which male-biased size dimorphism is more frequent, such as carnivores (Otariidae, Felidae, Canidae), primates (Hominidae, Cercopithecidae) and ungulates (Bovidae, Cervidae), are also those where adulticide was more prevalent in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Male adulticide was significantly and positively associated with male-biased size dimorphism in all analyses (table 1), being more prevalent in dimorphic species than in monomorphic ones (61% versus 44%, respectively, using 10% size difference between sexes as a cut-off point to consider a given species as dimorphic) [24]. Sexual size dimorphism is considered a direct consequence of sexual selection in mammals [24,25], and it is widely used as a surrogate of the intensity of the sexual selection operating on each species [25]. Mammals for which male-biased size dimorphism is more frequent, such as carnivores (Otariidae, Felidae, Canidae), primates (Hominidae, Cercopithecidae) and ungulates (Bovidae, Cervidae), are also those where adulticide was more prevalent in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The results of my analysis of sexual size dimorphism in primates are consistent with reproductive skew theory: in large groups, males may lose control of the sexual behaviour of the other members of the group or may concede reproductive opportunities to others. Another explanation is that sexual size dimorphism may have evolved before the evolution of polygyny, due to the effects of natural selection (Cassini 2019). There are several evolutionary mechanisms that can explain the evolution of sexual size dimorphism by natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, I found that sexual disturbance is frequent in four mammalian orders and eight families, which are also the most sexually dimorphic and polygynous among mammals (Ralls 1977, Cassini 2020). Taking into account the conclusions of Smuts and Smuts (1993), this review suggests that sexual coercion behaviour, which benefits males and harms females, is systematically present in colonial pinnipeds (mainly family Otariidae) and in the families Hominidae and Cercopithecidae within Primates.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, joining female groups appears to reduce sexual disturbance. Cassini (2020) suggested that this benefit to females could have elicited a positive feedback loop on the evolution of polygyny in mammals: females aggregated to avoid the costs of disturbance; this in turn facilitated female monopolisation, leading to increased reproductive success of dominant males, increasing the intensity of intrasexual selection, and promoting the evolution of higher levels of polygyny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation